Efektivitas Audio-Visual Dangers of Smoking dalam Meningkatkan Pengetahuan, Efikasi Diri dan Sikap Remaja di SMP Negeri 32 Kota Samarinda - Feriyanti, Alma; B, Ismail A; Ifroh, Riza Hayati (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2020)
Background. Indonesian Basic Health Research (2018) shown that the prevalence smoker aged ≥10 years old it was 28.8% and smoker between 10-18 years old increased from 7.2% to 9.1%. Objective. The objective of this study is to analyze the effectiveness of lecture videos with teaching aids the dangers of smoking to increase knowledge, self-efficacy and negative attitude towards smoking to adolescent. Method. This study used pre-experimental research with one group pre-test-post-test design. Statistical result of knowledge by Wilcoxon signed-rank test and Statistical result of self-efficacy and attitude by paired t-test. Result. Knowledge variables shown that p-value (0.000) < 0.05. There was a difference in the result of adolescent knowledge before and after intervention lecture videos on the dangers of smoking. Self-efficacy and attitude variable showed that p-value (0,023) and (0,019) < 0,05. There was a difference between the result of adolescent self-efficacy and attitude before and after intervention lecture videos the dangers of smoking. Conclusion. Lecture videos with teaching aid "dangers of smoking" are effective in improving student knowledge, self-efficacy, and attitude towards the dangers of smoking.